The Kingdom of Idalion in the Light of New Evidence - Hadjicosti, Maria (Bulletin of ASOR, 1997)
Idalion lies in the center of Cyprus, near the copper mines of the eastern Troodos foothills. The earliest settlement dates to the late 13th-early 12th century B. C. Its prosperous economy probably depended on copper exploitation and on trade with the coastal cities of Enkomi and Kition. The early Iron Age has been attested by tomb groups and unstratified pottery, but not yet by architectural remains. However, archaeological excavations conducted near the ancient town since the 19th century have revealed architectural, numismatic, and epigraphic evidence for Idalion in the Archaic and Classical periods. Foreign imports and Phoenician influence in art and artifacts point to trade between Idalion and the outside world. A large building complex, excavated by the Department of Antiquities of Cyprus in 1991-1995, has been identified as the Phoenician administrative center, dated to the fourth century B. C. The identification is supported by two groups of Phoenician inscriptions found on the floor of three rooms in two areas of the building.